Effect of matrix ductility on the compression behavior of steel-reinforced engineered cementitious composite columns. Issue 10 (July 2019) - Yuan, Fang; Chen, Mengcheng
Engineered cementitious composites have the characteristics of tensile strain hardening and multiple cracking. Substituting concrete with engineered cementitious composites can effectively avoid the cracking and durability problems induced by concrete brittleness. In this study, four steel-reinforced columns with various matrix types and load eccentricities were tested under eccentric compression. Test results indicated that steel-reinforced engineered cementitious composite columns exhibited a larger load-carrying capacity, higher ductility, better crack control ability, and damage tolerance, compared to reinforced concrete columns. All columns finally failed in compression as manifested by matrix crushing. However, the failure patterns between steel-reinforced engineered cementitious composite columns and reinforced concrete columns were extremely different. Significant concrete spalling appeared in the reinforced concrete columns, while no sign of engineered cementitious composite spalling was observed in the steel-reinforced engineered cementitious composite columns owing to the fiber bridging effect of engineered cementitious composite. The maximum crack width in reinforced concrete column increases almost linearly with the applied load and reaches 2 mm at most just prior to attaining the ultimate strength, while the maximum crack width in the steel-reinforced engineered cementitious composite column first increases and thereafter remains constant at approximately 60 μm with an increasing compression load. In addition to experimental work, a finite element model was proposed to predict the load–deformation response of the steel-reinforced engineered cementitious composite column. The prediction results are in close agreement with the test data. Finally, parametric studies were conducted to further illustrate the effects of matrix ductility and load eccentricity on the load–deformation curves, strain contour, and moment–load interaction curves of the columns.